Light and dark biofilm adaptation impacts larval settlement in diverse coral species - Paul A. O’Brien; Sara C. Bell; Laura Rix; Abigail C. Turnlund; Shannon R. Kjeldsen; Nicole S. Webster; Andrew P. Negri; Muhammad A. Abdul Wahab; Inka Vanwonterghem (Environmental Microbiome)
Abstract Background Recovery of degraded coral reefs is reliant upon the recruitment of coral larvae, yet the mechanisms behind coral larval settlement are not well understood, especially for non-acroporid species. Biofilms associated with reef substrates, such as coral rubble or crustose coralline algae, can induce coral larval settlement; however, the specific biochemical cues and the microorganisms that produce them remain largely unknown. Here, we assessed larval settlement responses in five non-acroporid broadcast-spawning coral species in the families Merulinidae, Lobophyllidae and Poritidae to biofilms developed in aquaria for either one or two months under light and dark treatments. Biofilms were characterised using 16S rRNA gene sequencing to identify the taxa associated with settlement induction and/or inhibition. Results We show that light and biofilm age are critical factors in the development of settlement inducing biofilms, where different biofilm compositions impacted larval settlement behaviour. Further, we show that specific biofilm taxa were either positively or negatively correlated with coral settlement, indicating potential inducers or inhibitors. Although these taxa were generally specific to each coral species, we observed bacteria classified as Flavobacteriaceae, Rhodobacteraceae, Rhizobiaceae and Pirellulaceae to be consistently correlated with larval settlement across multiple coral species. Conclusions Our work identifies novel microbial groups that significantly influence coral larval settlement, which can be targeted for the discovery of settlement-inducing metabolites for implementation in reef restoration programs. Furthermore, our results reinforce that the biofilm community on coral reef substrates plays a crucial role in influencing coral larval recruitment, thereby impacting the recovery of coral reefs.